Effectiveness of Learning using Web-Based Inquiry Based on Socioscientific Issues to improve students' understanding of Socioscientific Issues - Linda Kusumawati; Diana Rochintaniawati; Riandi Riandi (Postgraduate, University of Mataram, 2022)
The era of 21st-century learning requires students to have various abilities to overcome the complexities of society modern. This creates a breakthrough in learning by implementing an inquiry approach using a web-based socio scientific issue. Learning supported by the use of web-based inquiry can be accessed and implemented online and offline so that learning can become blended learning. The socio scientific issue raised in this study because to determine the level of students' knowledge of the problems in their environment. Samples that were used in this study were 32 junior high school students who were selected by random sampling technique in class. The research method used is a time series design where the pretest and posttest are carried out twice on different materials, namely water pollution and air pollution. Data analysis using normalized gain to determine the effectiveness of the use of web-based inquiry based on socio scientific issues. Based on this research, the average value of the first pretest is 17.53 and the posttest has increased to 26.78 so that the normalized gain value is 0.41 with the following criteria:Â currently. In the second pretest, the average score of students is 19 with the post-test average being 39.94 so the normalized gain obtained is 0.57 with moderate value criteria. The aspect of the value of socio scientific ability is also an issue measured by the results. In the first pretest and posttest with the topic of water pollution, aspects of evaluating information experienced an increase with a normalized gain value of 0.44 with moderate criteria, and the pretest and posttest values â€‹â€‹of the aspects of making decisions also increased with a normalized gain value of 0.39 with moderate criteria. On the pretest and the second post-test with the topic of air pollution aspects of evaluating issues have increased with a gain value Normalized value is 0.54 with moderate criteria, and for the aspect of making decisions to increase the normalized gain is 0.59 with moderate criteria.